2018
DOI: 10.1073/pnas.1800938115
|View full text |Cite
|
Sign up to set email alerts
|

eIF1 Loop 2 interactions with Met-tRNA i control the accuracy of start codon selection by the scanning preinitiation complex

Abstract: The eukaryotic 43S preinitiation complex (PIC), bearing initiator methionyl transfer RNA (Met-tRNA) in a ternary complex (TC) with eukaryotic initiation factor 2 (eIF2)-GTP, scans the mRNA leader for an AUG codon in favorable context. AUG recognition evokes rearrangement from an open PIC conformation with TC in a "P" state to a closed conformation with TC more tightly bound in a "P" state. eIF1 binds to the 40S subunit and exerts a dual role of enhancing TC binding to the open PIC conformation while antagonizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…The last insertion in CneIF1 extends a loop facing the solvent-exposed surface of SceIF1. Collectively, this shows that there are likely major differences in the eIF1-tRNAi interaction surface in Cryptococcus relative to other fungi, an interaction critical for start codon selection (63).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The last insertion in CneIF1 extends a loop facing the solvent-exposed surface of SceIF1. Collectively, this shows that there are likely major differences in the eIF1-tRNAi interaction surface in Cryptococcus relative to other fungi, an interaction critical for start codon selection (63).…”
Section: Resultsmentioning
confidence: 96%
“…The N-proximal loop insertion of CneIF1 extends from the SceIF1 sequence (18-DETATSNY-25) that contacts the acceptor arm of tRNAi. The CneIF1 insertion in loop 2 extends the SceIF1 loop 2 (70-KDPEMGE-76) that contacts the D-loop of tRNAi; substitutions D71A/R and M74A/R increase the charge of SceIF1 loop 2 and increase initiation at UUG codons and weak AUG codons (63). CneIF1 loop 2 has substitutions at both these functionally important sites, and is extended by a further 14 hydrophobic and negative residues.…”
Section: Resultsmentioning
confidence: 99%
“…The β-hairpin loops 1 and 2 of eIF5-NTD make extensive, favorable contacts with the Met-tRNA i , and because eIF5 loop-2 is shorter/more basic and oriented away from the Met-tRNA i , it avoids the electrostatic clash with the tRNA i D-loop predicted for the larger/more acidic loop-2 of eIF1 that projects toward the tRNA i (Figure 2C). Supporting this view, we recently demonstrated that substituting acidic and bulky hydrophobic residues in eIF1 loop-2 with alanines or basic residues increases UUG initiation in vivo and stabilizes TC binding to the PIC at UUG codons, as would be expected from eliminating electrostatic/steric clashing, or introducing electrostatic attraction, between eIF1 loop-2 and tRNA i , which removes an impediment to the P IN state to enhance selection of a near-cognate start codon (Thakur and Hinnebusch, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Another notable difference between eukaryotic and archaeal e/aIF2 and their homologues corresponds to the absence of the acidic loop 2 in the archaeal kingdom, as observed here and in ( 46 ). In eukaryotes, the acidic loop 2 was shown to participate in start codon selection by interacting with the D-stem-loop of the initiator tRNA ( 17 , 58 ). In addition, many archaeal aIF1 possess a zinc-binding knuckle in their N-terminal domain whereas this is never observed in eukaryotic species.…”
Section: Discussionmentioning
confidence: 99%